Comparison of risk-scoring systems in predicting hospital mortality after abdominal aortic aneurysm repair - Chaiyarat Supsamutchai (2018)
OBJECTIVE: To compare the Physiological and Operative Severity Score for the enUmeration of Mortality and Morbidity, Portsmouth adjustment (P-POSSUM), the Hardman index and the Glasgow aneu- rysm score (GAS) in the prediction of hospital mortality after abdominal aortic aneurysm (AAA) repair. METHODS: Medical charts of 146 AAA patients treated between January 1996 and January 2007 were reviewed. The P-POSSUM, Hardman index and GAS were calculated for each patient. The scores were tested and compared for their discriminatory ability to predict hospital death. RESULTS: Of the 146 patients with ruptured and unruptured AAAs (133 underwent open repair, five underwent extra-anatomical bypass and eight underwent endovascular aneurysm repair), 18 died (12%) after AAA repair. The areas under the receiver operating characteristic curves for the GAS, Hardman index and P-POSSUM for predicting hospital mortality were 0.740, 0.730 and 0.886, respectively. The area under the receiver operating characteristic curve for the P-POSSUM was significantly higher than those of other scores. CONCLUSION: In the present study, the P-POSSUM was the best predictor of hospital mortality for patients undergoing AAA repair. © 2009 Pulsus Group Inc. All rights reserved.